Reversible Deactivation Radical Polymerization Synthesis and Applications of Functional Polymers - Mays, Jimmy W.; Mays, Jimmy W.; Singha, Nikhil K.; Singha, Nikhil K. (De Gruyter, 2020)
This book describes strategies and mechanism of reversible deactivation radical polymerization (RDRP) to synthesize functional polymers. Several approaches such as atom transfer radical polymerization and the combination of click chemistry and RDRP are summarized. Contributors from interdisciplinary fields highlight applications in nanotechnology, self-healing materials, oil and water resistant coatings and controlled drug delivery systems.